Hackathon: The power of information exchange and learning - Sanz-Martos, Sandra (Anuario ThinkEPI, 2017)
Hackathons are going beyond the technological interests to reach the social ones. This undoubtedly upward trend allows the exchanging of information and experiences, learning and creating knowledge collectively, solving problems, and responding to the needs of society. Hackers have been programming and solving problems collaboratively for decades. Citizen hackathons have been adapted to solve social problems. Its organizational structure, which implies horizontal and intensive dynamics, allows the participants to complement their individual experiences and skills and to develop specific solutions.